Shea (Vitellaria paradoxa C.F.Gaertn.) seedlings recovery after fire: gas-exchange, growth and biomass partitioning assessment. Issue 3 (3rd July 2019) - Tom-Dery, Damian; Jensen, Kai; Reisdorff, Christoph
ABSTRACT: Shea ( Vitellaria paradoxa C.F. Gaertn) is native to the savanna ecosystem, an ecosystem prone to periodic bushfires due to the long dry season and accumulated combustible biomass. We studied the effects of simulated fire on shea seedlings gas exchange, growth and biomass allocation in a greenhouse experiment. We hypothesized that fire decreases photosynthetic performance of regrown leaves leading to lower growth and altered biomass allocation in shea seedlings. Sixteen weeks after fire treatment, none of the measured photosynthetic, growth and biomass parameters showed a significant difference between fire treated seedlings and, control seedlings. Shea seedlings have therefore shown exceptional recovery of gas exchange performance, growth and biomass allocation patterns 4 months after fire.